Impact of childhood cerebellar tumor surgery on cognition revealed by precuneus hyperconnectivity. Issue 1 (13th April 2022) - Dorfer, Christian; Pletschko, Thomas; Seiger, Rene; Chocholous, Monika; Kasprian, Gregor; Krajnik, Jacqueline; Roessler, Karl; Kollndorfer, Kathrin; Schöpf, Veronika; Leiss, Ulrike; Slavc, Irene; Prayer, Daniela; et al.
Abstract: Background: Childhood cerebellar pilocytic astrocytomas harbor excellent overall survival rates after surgical resection, but the patients may exhibit specific cognitive and behavioral problems. Functional MRI has catalyzed insights into brain functional systems and has already been linked with the neuropsychological performance. We aimed to exploit the question of whether resting-state functional MRI can be used as a biomarker for the cognitive outcome assessment of these patients. Methods: We investigated 13 patients (median age 22.0 years; range 14.9-31.3) after a median interval between surgery and examination of 15.0 years (range 4.2-20.5) and 16 matched controls. All subjects underwent functional 3-Tesla MRI scans in a resting-state condition and battery neuropsychological tests. Results: Patients showed a significantly increased functional connectivity in the precuneus compared with controls ( P < .05) and at the same time impairments in various domains of neuropsychological functioning such as a lower mean Wechsler Intelligenztest für Erwachsene (WIE) IQ percentile (mean [M] = 48.62, SD = 29.14), lower scores in the Trail Making Test (TMT) letter sequencing (M = 49.54, SD = 30.66), worse performance on the WIE subtest Digit Symbol Coding (M = 38.92, SD = 35.29), subtest Symbol Search (M = 40.75, SD = 35.28), and test battery for attentional performance (TAP) divided attention task (M = 783.92, SD = 73.20). Conclusion: Childhood cerebellar tumor treated by resection only strongly impacts the development of precuneus/posterior cingulate cortex functional connectivity. Functional MRI has the potential to help deciphering the pathophysiology of cerebellar-related cognitive impairments in these patients and could be an additional tool in their individual assessment and follow-up.